The Role of Patient Factors, Cancer Characteristics, and Treatment Patterns in the Cost of Care for Medicare Beneficiaries with Breast Cancer. (29th June 2015) - Xu, Xiao; Herrin, Jeph; Soulos, Pamela R.; Saraf, Avantika; Roberts, Kenneth B.; Killelea, Brigid K.; Wang, Shi‐Yi; Long, Jessica B.; Wang, Rong; Ma, Xiaomei; Gross, Cary P.
Abstract : Objective: To characterize Medicare expenditures on initial breast cancer care and examine variation in expenditures across hospital referral regions (HRRs). Data Source: We identified 29, 110 women with localized breast cancer diagnosed in 2005–2008 and matched controls from the Surveillance, Epidemiology, and End Results‐Medicare linked database. Study Design: Using hierarchical generalized linear models, we estimated per patient Medicare expenditure on initial breast cancer care across HRRs and assessed the contribution of patient, cancer, and treatment factors to regional variation via incremental models. Principal Findings: Mean Medicare expenditure for initial breast cancer care was $19, 255 per patient. The average expenditures varied from $15, 053 in the lowest‐spending HRR quintile to $23, 480 in the highest‐spending HRR quintile. Patient sociodemographic, comorbidity, and tumor characteristics explained only 1.8 percent of the difference in expenditures between the lowest‐ and highest‐spending quintiles, while use of specific treatment modalities explained 14.5 percent of the difference. Medicare spending on radiation therapy differed the most across the quintiles, with the use of intensity modulated radiation therapy increasing from 1.7 percent in the lowest‐spending quintile to 11.6 percent in the highest‐spending quintile. Conclusions: Medicare expenditures on initial breast cancer care vary substantially across regions. Treatment factors are major contributors to the variation.